Bravo two zero - McNab, Andy (BCA, 1993)
The true story of the most famous SAS operation in history. 'Bravo Two Zero' was the code-name of the famous SAS operation: a classic story of bravery in the face of overwhelming odds. BRAVO TWO ZERO by patrol commander 'Andy McNab' became an international bestseller, as did the book by 'Chris Ryan' (THE ONE THAT GOT AWAY). Both men became millionaires. Three members of the patrol were killed. One, veteran sergeant Vince Phillips, was blamed in both books for a succession of mistakes. As Michael Asher reveals, the stories in BRAVO TWO ZERO and THE ONE THAT GOT AWAY grew considerably in the telling. Their heroic tales of taking out tanks with their rocket launchers, mowing down hundreds of Iraqi soldiers, the silent stabbing of the occasional sentry, were never mentioned at their post-war debriefings...In an investigation literally in the footsteps of the patrol, Michael Asher tells the true story.